प्राचीन भारतीय वाङ्मयमे अंतर्निहित आर्थिक अवधारणा सभ - Brajendra Kumar Jha; Shailendra Kumar Jha (My University, 2021)
Various branches of knowledge have been discussed in detail in ancient Indian texts. Different studies have been undertaken from time to time in relation to most of these fields. Unfortunately, there has been no serious research that was initiated on the economic concepts described under them till date. The present book will make it easier to understand the basic principles of Indian economics.
Prachin Bhartiya Vangmay Me Antarnihit Aarthik Avadharnayen
Keywords: Maithili